(untitled) (Research, Society and Development, 2025)
The increasing irregular occupation of riverbanks in urban areas has exacerbated conflicts between territorial expansion and environmental conservation, especially in small municipalities. In Brazil, the enactment of Law No. 14.285/2021, by relaxing the parameters for the definition of urban Permanent Preservation Areas (PPAs), transferred the responsibility for this regulation to the municipalities, raising concerns about their institutional capacity for implementation. In this context, this study aimed to analyze the socio-environmental impacts of irregular constructions along the banks of the Araguaia River, in the municipality of Araguatins, State of Tocantins (TO), Brazil, in light of the provisions of the new legislation. The research, with a qualitative and descriptive approach, was based on documentary analysis, georeferenced field observation and discursive textual analysis. The results reveal the existence of recent constructions on the river bed without environmental licenses, as well as the consolidation of a social imaginary that tends to normalize the irregular occupation of the riparian zones. It was also observed that the absence of updated master plans and weak municipal oversight compromises environmental governance and the integrity of riparian ecosystems. This research contributes to the debate on urban planning and sustainability by highlighting the need for coordinated efforts between legal regulation, environmental planning and social participation in the management of vulnerable territories.